Type 2 diabetes mellitus and vitamin metabolism: Vitamins in type 2 diabetes - Sert, Tuğba; Arslan, Şule (Journal of Surgery and Medicine, 2025)
Type 2 Diabetes Mellitus (T2DM) is a disease characterized by chronic hyperglycemia and oxidative damage, leading to harm in tissues and organs. Studies have shown a relationship between increased oxidative stress, decreased insulin sensitivity, and the effectiveness of antioxidant therapy in managing T2DM. Early diagnosis, lifestyle changes, drug therapy, and vitamin supplements are essential in managing T2DM. Antioxidant vitamins, in particular, are crucial for reducing oxidative stress caused by T2DM and minimizing related complications.